1991
DOI: 10.1111/j.1600-0447.1991.tb01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of early parenting in panic and agoraphobia

Abstract: Thirty-two patients with a DSM-III-R diagnosis of panic disorder (PD) were administered the Parental Bonding Instrument (PBI), a 25-item self-report questionnaire devised to evaluate parental rearing practices. Compared with 32 matched healthy controls, PD patients scored both their parents as being significantly less caring and more overprotective. Moreover, the consistency of parental attitudes between the 2 parents was significantly lower, indicating lesser uniformity in the rearing patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
2
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 24 publications
4
32
2
2
Order By: Relevance
“…This finding corroborates previous studies that evaluated the relationship between parental bonding and anxiety disorders. [17][18][19]34 A study that was held in six European countries reported a parenting pattern comprising less parental warmth and maternal overprotection associated with different anxiety disorders. 35 Lower parental care has been associated with PD in two other cultures, 18,19 but we were not able to replicate this association in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding corroborates previous studies that evaluated the relationship between parental bonding and anxiety disorders. [17][18][19]34 A study that was held in six European countries reported a parenting pattern comprising less parental warmth and maternal overprotection associated with different anxiety disorders. 35 Lower parental care has been associated with PD in two other cultures, 18,19 but we were not able to replicate this association in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…16 Some authors have described that PD patients reported less care and more protection by both parents as compared to control subjects. [17][18][19] Pacchierotti et al observed less care and more protection regarding the paternal figure, whereas considering the maternal figure, there were less careful and less protective patterns. 20 To our knowledge, there are no available data in the literature about the role of the quality of parental bonding, assessed by the Parental Bonding Instrument (PBI), and childhood trauma, assessed by the Childhood Trauma Questionnaire (CTQ), and PD in adulthood in South American countries, which are culturally different from European and North American countries.…”
Section: Introductionmentioning
confidence: 99%
“…Arrindell et al 1983;Arrindell et al 1989;Parker 1979). However, results for 'over-protection' are inconsistent, with some studies reporting more over-protection by both parents (Faravelli et al 1991; Wiborg and Dahl 1997) or by the mother (Parker et al 1997;Silove et al 1991) for the offspring of parents with panic disorder during comparisons with the offspring of diagnosis free parents, whereas other studies could not find an association (Arrindell et al 1983;Arrindell et al 1989;Parker 1979).Early observational studies have analysed the ongoing interaction between the parent with an anxiety disorder and their child (with or without assessment of child diagnosis). However, these studies used groups of patients with mixed anxiety disorders instead of "pure" groups of parents with panic disorder.…”
mentioning
confidence: 90%
“…Faravelli et al [36] found that PD patients scored both their mother and father as being significantly less caring and more protective than did the controls, and the differences were more pronounced for the mother. In a sample of PD patients without agoraphobia, Silove et al [37] found that the only significant difference was the higher maternal protection scores in the PD group.…”
Section: The Parental Bonding Instrument and Pdmentioning
confidence: 99%
“…A back-translation of the PBI showed that in the Italian version, the original meaning was retained, and a pilot calibration study showed that the original independence of the two dimensions was maintained (care vs. protection: r = 0.16 for mothers and r = 0.08 for fathers) [36]. As the PBI mainly explores qualitative features of parental bonding and there is a lack of instruments investigating quantitative and objective characteristics, ten additional items were drawn up in order to explore these aspects of infant care, and these were administered together with the PBI.…”
Section: Assessmentmentioning
confidence: 99%